Modelo de flujo bilineal con transferencia interporosa transitoria - Valdés Pérez, Alex Rodrigo (My University, 2012)
Modelo de flujo bilineal con transferencia interporosa transitoria
Modelo de flujo bilineal con transferencia interporosa transitoria
Keywords: Modelo de flujo bilineal con transferencia interporosa transitoria